DEVELOPMENT STUDENT WORKSHEET GUIDED INQUIRY ORIENTED TO TRAIN STUDENT CREATIVE THINKING SKILLS IN MATTER ACID BASE INDICATOR BASED ON NATURAL PRODUCT (Universitas Negeri Surabaya, 2018)
The aim’s of this research was to develop student worksheet guided inquiry oriented to train student creative thinking skills of acid base indicator matter based on natural product. The feasibility of student worksheet that developed assessed from criteria the validity, practicality, and effectiveness. This research used Research and development (R&D) model that limited until stage of preliminary field. The feasibility of student worksheet in terms of validity is obtained based on assessment by validator consisting of two chemistry lecturers and one chemistry subject teacher. The validation by experts about content validity and construct validity obtained a percentage in a row that is 85,93% and 92.22% with the category is very valid. The feasibility of the practicality criteria assessed from responses of student who get a positive response of 99,21% with a very practical category, supported by the observation of student activities during learning that obtained average relevant activity 98.39% on very good interpretation. The feasibility of effectiveness criteria assessed from result student creative thinking test that show all students get the above of minimum learning completeness ≥76 with student creative thinking skill on aspect originality obtained the average percentage of 94,67%, fluency 86,67%, and flexibility 80% on high category.Keywords: Students Worksheet, Guided Inquiry, Creative Thinking Skills, Acid Base Indicator, Based on Natural Product.